A review of heterogeneous calcium oxide based catalyst from waste for biodiesel synthesis - Ling, Jasmine Si Jie; Tan, Yie Hua; Mubarak, Nabisab Mujawar; Kansedo, Jibrail; Saptoro, Agus; Nolasco Hipolito, Cirilo (SN Applied Sciences, 2019)
Biodiesel is one of the most promising method to replace the fossil fuels because it is more environmentally friendly. Nevertheless, biodiesel manufacturing costs are much higher compared to conventional fossil fuels. Thus, the biodiesel should be synthesizing from reusable wastes to minimize the production cost. Homogeneous catalyst is the most common catalyst employed in the commercial biodiesel field. However, there are some drawbacks in using homogeneous catalyst in the reaction such as the difficulties faced in separation process of the homogeneous catalyst from the mixture of product. The presence of promising current technology has proved that the utilization of heterogeneous catalyst can assist in overcoming the existing problem of homogeneous catalytic reaction, especially in wastewater generation. The heterogeneous catalysts are more environmentally friendly, easier to separate and its reusability property. Despite its low production cost and its beneficial use as an eco-friendly waste recycle method, waste materials may possess qualities and characteristics that differ from the conventional homogeneous catalyst prior to biodiesel production. This review paper focused in the recent discovery of the heterogeneous catalyst synthesized from natural bio-waste materials, especially CaO-based such as eggshells, seashells and bones for biodiesel production. Apart from that, gypsum, part of the construction waste is proposed as the newly found heterogeneous catalyst. Gypsum exists abundantly due to the rapid development of the economics where construction and demolition activities are happening daily. The utilization of these construction waste-based catalysts may able to provide a sustainable route for biodiesel production. This review will enhance the development and existing scientific data in the area of biodiesel production and the synthesis of CaO-based catalyst especially the synthesis of CaO-based catalysts from construction material.
Keywords: Biodiésel sustentable; Catalizadores heterogéneos; Residuos de construcción